A Study on the Prevalence of Anemia among School Children in Karimnagar Telangana - Dr. K. Manisha; Mohd Danish Raza; Shaguftha Afreen S; Amane, Shital; Shaguftha Nazneen; Khinchi, Sripathi Greeshma (Asian Journal of Pharmaceutical Research and Development, 2026)
Anemia and poor nutritional status are major health concerns among school-aged children. Nutritional deficiencies and socioeconomic factors play a key role in their occurrence. Anemia can adversely affect growth, health, and academic performance. Assessing nutritional status and anemia prevalence is essential for early detection and effective intervention. A mixed methods approach using questionnaires, interviews, and observations will be necessary to gather information for the paper. Depending on the level of clarity required, the sample size will then be approximated over the course of 20 weeks using descriptive statistics and thematic analysis. The study found that schoolchildren had a high prevalence of anemia (51.6%), with females being more affected than boys. Compared to children with normal BMI, underweight children had a higher prevalence of anemia. While a significant percentage of participants were under weight and obese, the majority had normal nutritional status. These results highlight the significance of early risk factor identification, dietary evaluation, and routine screening. Reducing anemia and enhancing general child health can be achieved in large part by providing nutrition programs, dietary education, and preventive measures